(untitled) (Medical Forum Monthly, 2024)
Objective: To investigate the association between arteriovenous fistula (AVF) creation and hemoglobin levels in hemodialysis-dependent end-stage renal disease (ESRD) patients. Study Design: A cross-sectional study Place and Duration of Study: This study was conducted at the Central Park Medical College and Teaching Hospital in collaboration with Department of Nephrology, Choudhary Muhammad Akram Teaching Hospital, Lahore from December 2022 to June 2023. Methods: Patients on hemodialysis were included, while those on peritoneal dialysis or not undergoing dialysis were excluded. Sociodemographic details, medical history, and dialysis access information were recorded. Hepatitis B and C screening was performed, and vascular access was categorized into AVF and lines. Hemoglobin levels were assessed, and statistical analysis was conducted using SPSS version 26. Results: Out of 72 ESRD patients, 37.5% had AVF, and 62.5% had access via lines. Hemoglobin levels were significantly higher in patients with AVF (mean Hb ≈ 9.26 g/dL) compared to those without AVF (mean Hb ≈ 8.07 g/dL) with a p-value of 0.003. AVF presence was associated with a lower rate of infections (7.40%) compared to patients without AVF (60%) with a p-value of 0.0001. Conclusion: Arteriovenous fistula (AVF) may be associated with higher hemoglobin levels and a reduced risk of infections in hemodialysis-dependent end-stage renal disease (ESRD) patients.